Design and Development of Power Electronic Controller for Grid-connected PV Array - T. Shanthi (International Journal of Applied Power Engineering (IJAPE), 2012)
Design and simulation of a simple power electronic interface for grid-connected PV array has been proposed using boost converter and line-commutated inverter with maximum power point tracking (MPPT) controller. The output of PV array varies with irradiation, and hence the duty cycle of the PI controller is adjusted automatically to supply a constant DC voltage to the inverter circuit, the output of which is directly connected to the grid. The MPPT controller extracts maximum power from the solar array and feeds it to the single-phase utility grid. The proposed scheme has been modeled in the MATLAB 7.1 software and the complete system has been simulated for open loop and closed loop configurations. The active power fed to the grid is taken for different firing angles in open loop mode and the firing angle for maximum power has been determined. This is compared with the firing angle obtained from the closed loop mode and found that both results agree with each other.